Gold Nanostars Functionalized with a D-Peptide Promote Disaggregation and Improve Detection of Amyloid-Β Fibrils: In Vitro and in Vivo Studies - Melo-Hurtado, F (Elsevier Ltd, 2025)
Gold nanostars (AuNS) provide remarkable advantages for disease diagnosis and therapy. AuNS offer a superior platform for surface-enhanced spectroscopy, and recent findings indicate that their spikes allow unique interactions with protein aggregates, making their use in the detection and therapy of amyloid aggregates promising, although still in nascent stages. This study investigated the development of a nanosystem utilizing AuNS and the D1 peptide for the disaggregation and enhanced detection of amyloid-β (Aβ) aggregates, both in vitro and in vivo. This AuNS-D1 nanosystem was constructed via covalent attachment of the peptide, exhibiting optical and surface properties suitable for bioapplications. The effectiveness of an AuNS-based nanosystem in disaggregating Aβ fibrils was demonstrated for the first time through incubation at a defined concentration range. The AuNS-D1 nanosystem improved the detection of Aβ fibrils using the thioflavin probe due to the fluorescence surface-enhanced effect. In vivo assays indicated that the AuNS-D1 nanosystem exhibits superior disaggregating efficacy on the amyloid load in a transgenic Caenorhabditis elegans model compared to the D1 peptide, evidenced by a reduction in both the number and size of the amyloid load following the incubation of the nematodes with AuNS-D1. These results are encouraging and suggest that AuNS-D1 may serve as an effective diagnostic and therapeutic agent for amyloid-related diseases, including Alzheimer s disease. © 2024 Elsevier Ltd